Redes sociales en los adultos mayores beneficiarios del centro “Casa Somos” de La Roldós- Pisulí, en el periodo de marzo-julio 2016 - Sandoval Sánchez, María Cristina (2017)
The present exploration aims to analyze how the social networks of the group of Older Adults of the Casa Somos Center of La Roldós-Pisulí are organized in the period March to July of 2016 and their appreciation of the support that these networks provide them. This work is part of the macro research called "Cognitive development, quality of life and subjective perception of aging" that is being carried out by the Psychology Degree at the Universidad Politécnica Salesiana (Heredia, 2015-2017). The methodology used in the research was quantitative, based on the application of standardized tests: ERASAM and MOS Scale. The results showed that the family network is the one with the highest density; however, the greatest emotional support is provided by the informal extra familiar network; the institutional network does not have a significant presence when providing informative, instrumental, material or emotional support. The perception of support shows that extra familiar support, represented by neighbors and the group of older adults, is still more significant.